FRI0487 Apremilast is associated with long-term (4-YEAR) DAS-28 (CRP) remission and improvements in skin disease: results from a phase iii study in dmard/biologic-experienced patients with active psoriatic arthritis. (15th June 2017) - Edwards, CJ; Blanco, FJ; Crowley, J; McIlraith, M; Paris, M; Delev, N; Teng, L; Birbara, CA
Abstract : Background: Treatment goals for long-term control of skin and joint symptoms in active psoriatic arthritis (PsA) include clinically important changes in DAS-28 (CRP), achievement of remission in DAS-28 (CRP), reduction in swollen joint count (SJC), and decrease in skin disease. 1 PALACE 3 included PsA patients with active joint disease and an active skin lesion at the time of enrollment. Objectives: Report the impact of apremilast (APR) on PsA manifestations over 4 years. Methods: Patients were stratified by baseline (BL) DMARD use (yes/no) and psoriasis involvement of the body surface area (<3%/≥3%) and randomized (1:1:1) to placebo (PBO), APR 30 mg BID (APR30), or APR 20 mg BID (APR20). After the 24-week PBO-controlled phase, all patients were treated with APR30 or APR20 and could enroll in the long-term extension. Efficacy assessments were conducted through Week 208. Results: 505 patients were randomized and received ≥1 dose of study medication (PBO: n=169; APR30: n=167; APR20: n=169). A total of 91% (227/249) of patients starting the fourth year of APR therapy completed the Week 208 visit. Patients treated with APR30 demonstrated sustained decreases in disease activity at Week 208, as shown by mean change from BL in DAS-28 (CRP) of −1.66; 80.3% achieved good/moderate EULAR response and 50.4% achieved DAS-28 (CRP) remission. Sustained effect on inflammation at Week 208 was also demonstrated by mean/median percent changes in SJC, a marker of inflammatory activity, of −77.4%/−100.0% (Table); 64.8% of patients had an SJC of 0 or 1. Decreases in disability and maintenance of functionality were shown by sustained improvements in Health Assessment Questionnaire-Disability Index (HAQ-DI) scores (Table). A continued effect on skin disease was shown by decreases in skin involvement, as measured by the Psoriasis Area and Severity Index (PASI); 54.7% of APR30 patients had BL PASI >5 and 27.3% had BL PASI >10; at Week 208, 64.5% had PASI <3 and 77.4% had PASI ≤5. PASI-75 and PASI-50 response rates also demonstrated clinically significant relief (Table). In patients treated with APR20, similar findings were observed at Week 208. No new safety concerns were identified through 208 weeks of APR30 therapy. During Weeks >156 to ≤208 of APR30 exposure, the only adverse event (AE) occurring in ≥5% of patients was nasopharyngitis; most AEs were mild or moderate in severity. Serious AEs occurred in 7.2% of APR30 patients over Weeks >156 to ≤208, similar to rates in earlier study periods. Few discontinuations due to AEs (0.7%) occurred over Weeks >156 to ≤208. The APR20 safety profile was similar to that of APR30. Conclusions: Over 208 weeks, APR demonstrated sustained and clinically important improvements in PsA signs and symptoms, including physical function and associated psoriasis, among patients continuing the study. APR was generally well tolerated with an acceptable safety profile. References: Gossec L, et al. Ann Rheum Dis. 2016;75:499–510. Disclosure of Interest: C. Edwards Grant/research support from: Celgene Corporation, Pfizer, Roche, Samsung, Consultant for: Celgene Corporation, Pfizer, Roche, Samsung, Speakers bureau: Abbott, GSK, Pfizer, Roche, F. Blanco Consultant for: Bioibérica, Gebro Pharma, Pfizer, J. Crowley Grant/research support from: AbbVie, Amgen, Celgene Corporation, Janssen, Merck, Pfizer, Consultant for: AbbVie, Amgen, Speakers bureau: AbbVie, M. McIlraith Employee of: Celgene Corporation, M. Paris Employee of: Celgene Corporation, N. Delev Employee of: Celgene Corporation, L. Teng Employee of: Celgene Corporation, C. Birbara Grant/research support from: Amgen, BMS, Incyte, Eli Lilly, Merck, Pfizer